INDONESIAN ISLAMIC EDUCATION: TOWARDS SCIENCE DEVELOPMENT - Ja'far, Handoko (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2015)
Education as the root of civilization has an important role in preparing human resources toward the effort of developing sciences. Nowadays, Moslem in the world are are divided into two attitudes: resisting and refusing the development of sciences. Both of the attitutes are needed to bridge wisely. It meant no one is burdened in facing modern sciences by the ways of appreciating the modern sciences, applying them appropriately and learning from the history of the development of knowledge in the glory age of Islam. This article tried to confirm that science as a result of education, is not only the representation of civilization but also the demonstration of the high value of civilization. In Indonesia, the idea to reconstruct the model of Islamic education is getting stronger in accordance with the development of modern education. In this context, the clasical knowledge as heritance needed to be transformed into the modern one. Transformation is something unavoidable by the institutions of Islamic education.***Pendidikan -sebagai akar peradaban- memiliki peran penting dalam menyiapkan sumber daya manusia menghadapi perkembangan ilmu. Saat ini, sikap umat Islam terbelah menjadi dua: menolak dan menerima perkembangan ilmu. Kedua sikap ini perlu ditengahi secara bijaksana. Caranya, merasa tidak terbebani dalam menghadapi sains modern dengan memberikan apresiasi dan menerapkannya secara benar. Di samping itu, dengan cara belajar dari sejarah perkembangan ilmu di masa kejayaan Islam. Artikel ini berusaha menegaskan bahwa ilmu pengetahuan sebagai buah dari pendidikan, tidak hanya menjadi representasi peradaban tetapi juga mampu menunjukkan tingginya nilai peradaban. Di Indonesia, gagasan untuk merekonstruksi model pendidikan Islam menguat seiring dengan perkembangan pendidikan modern. Dengan demikian, meskipun pengetahuan klasik merupakan warisan, namun perlu dilakukan transformasi ilmu yang selaras dengan dunia modern. Perubahan merupakan hal yang tidak dapat dihindari oleh lembaga pendidikan Islam.